Comparative genomic analysis of duplicated homoeologous regions involved in the resistance of Brassica napus to stem canker - Fopa Fomeju, Berline; Falentin, Cyril; Lassalle, Gilles; Manzanares-Dauleux, Maria J.; Delourme, Regine (Frontiers in Plant Science, 2015)
All crop species are current or ancient polyploids. Following whole genome duplication, structural and functional modifications result in differential gene content or regulation in the duplicated regions, which can play a fundamental role in the diversification of genes underlying complex traits. We have investigated this issue in Brassica napus, a species with a highly duplicated genome, with the aim of studying the structural and functional organization of duplicated regions involved in quantitative resistance to stem canker, a disease caused by the fungal pathogen Leptosphaeria maculans. Genome-wide association analysis on two oilseed rape panels confirmed that duplicated regions of ancestral blocks E, J, R, U and W were involved in resistance to stem canker. The structural analysis of the duplicated genomic regions showed a higher gene density on the A genome than on the C genome and a better collinearity between homoeologous regions than paralogous regions, as overall in the whole B. napus genome. The three ancestral sub-genomes were involved in the resistance to stem canker and the fractionation profile of the duplicated regions corresponded to what was expected from results on the B. napus progenitors. About 60% of the genes identified in these duplicated regions were single-copy genes while less than 5% were retained in all the duplicated copies of a given ancestral block. Genes retained in several copies were mainly involved in response to stress, signaling or transcription regulation. Genes with resistance-associated markers were mainly retained in more than two copies. These results suggested that some genes underlying quantitative resistance to stem canker might be duplicated genes. Genes with a hydrolase activity that were retained in one copy or R-like genes might also account for resistance in some regions. Further analyses need to be conducted to indicate to what extent duplicated genes contribute to the expression of the resistance phenotype.